2008
DOI: 10.1007/s12185-008-0222-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinicopathologic findings according to JAK2 V617F mutation in patients with essential thrombocythemia

Abstract: The JAK2 V617F mutation is present in most patients with polycythemia vera, but in fewer patients with essential thrombocythemia (ET). We have assessed the frequency of this mutation in ET patients using amplification refractory mutation system PCR and determined the relationship of the mutation with disease phenotypes. Clinical-laboratory findings and histomorphological features were compared according to mutational status in 108 ET patients. The mutation was detected in 61 patients (56.5%) including one homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…However, the present study results indirectly support the concept that the JAK2V617F mutation contributes to intrinsic changes in both megakaryocyte and platelet biology beyond the increase in cell numbers [35][36][37]. The results of another single center analyses also revealed that the JAK2 V617F (−) cases did not differ significantly from the JAK2 V617F (+) cases in the incidence of thrombosis [38][39][40]. The number of involved patients might be determinative in view of clear evaluation of the predictive value of the JAK2 V617F mutation in thrombosis [41,42].…”
Section: Discussionsupporting
confidence: 75%
“…However, the present study results indirectly support the concept that the JAK2V617F mutation contributes to intrinsic changes in both megakaryocyte and platelet biology beyond the increase in cell numbers [35][36][37]. The results of another single center analyses also revealed that the JAK2 V617F (−) cases did not differ significantly from the JAK2 V617F (+) cases in the incidence of thrombosis [38][39][40]. The number of involved patients might be determinative in view of clear evaluation of the predictive value of the JAK2 V617F mutation in thrombosis [41,42].…”
Section: Discussionsupporting
confidence: 75%
“…Korean patients with MPN had similar frequencies of JAK2 mutation and occurrence of vascular events as compared to Western patients (Bang et al. , 2009; Cho et al. , 2009).…”
Section: Discussionmentioning
confidence: 89%
“…The lower frequency of JAK2 V617F mutation in our data as compared with previous studies (Table 2) is hard to explain. Korean patients with MPN had similar frequencies of JAK2 mutation and occurrence of vascular events as compared to Western patients (Bang et al, 2009;Cho et al, 2009). However, the patterns of vascular events revealed notable differences; a very low incidence of venous thrombosis including SVT, more prevalent cerebrovascular events, and frequent serious bleeding complications at the time of diagnosis (Bang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…60 Other series in adults also showed that the presence of JAK2 mutation did not have a significant impact on the risk of thrombosis or lost its predictive value when other variables were controlled for in the analysis. 6166 A glaring common denominator of all these studies is the small sample size, which weakens the strength of conclusions.…”
Section: Driver Mutations and Thrombotic Risk In Patients With Etmentioning
confidence: 99%